(untitled) (EDUCATION IN THE 21ST CENTURY, 2023)
This article examines in detail the higher education systems of the Republic of Armenia (RA) and Denmark, identifying their similarities and differences in the areas of management, financing, and structure. It also presents ways to admit to the university and the existing types of grading. The purpose of this article is to review and study the higher education systems of the RA and Denmark in detail, as well as to conduct a comparative analysis to identify the characteristic features in the field of higher education management in these two countries. The results of this study are presented in the article in the form of a series of tables, where the obtained data show the similarities and differences between the systems of management and financing, grading and admission to universities in the RA and Denmark, indicating the distinctive features of the structures of higher education systems in these countries. As a result of a comparative analysis of the management of the systems of higher education in the RA and Denmark, we concluded that both state and intra-university bodies carried out the management of higher education in those countries, which are organized in the form of central and local self-government. However, control bodies have different names. There is an “academic freedom” both in the Armenian and in the Danish universities, more developed in Denmark. The forms of admission and student grading systems in the universities of these two countries are also different. Thus, in a result of a comparative analysis of the management of the higher education systems of the RA and Denmark, we identified the similarities and differences, advantages and disadvantages of both systems, which can help us apply the positive elements of the Danish higher education system to the Armenian one to improve the quality of the higher education in our country.